Cementum and dentin repair following root damage caused by the insertion of self-tapping and self-drilling miniscrews - Majid Ghanbarzadeh; Farzin Heravi; Reihaneh Abrishamchi; Hooman Shafaee; Narges Ghazi; Parya Heravi; Hamid Ghanbarzadeh (Wolters Kluwer Medknow Publications, 2017)
OBJECTIVE: The aim of this study was to evaluate the histological responses of cementum, root dentin, and pulp following intentional root injuries caused via self-tapping and self-drilling miniscrews. MATERIALS AND METHODS: Fourteen patients (with a mean age of 15.7 years and age range of 14-18 years) who were scheduled for the extraction of all four first premolars as part of their orthodontic treatment plan participated in this study. The roots of the right and the left quadrants' first premolars were designedly injured using self-tapping miniscrews and self-drilling miniscrews, respectively. Teeth were extracted eight weeks after the injury. Cementum repair was assessed through histological examinations. RESULTS: In this study, 40 teeth (75.4%) showed reparative cementum formation and 13 teeth (24.5%) showed no repair. There was no significant difference between the two groups regarding the formation of reparative cementum (P = 0.3). In all examined teeth, the inflammatory response of the pulp to the cold test was within the normal range. CONCLUSION: This study showed that in most cases, the healing of cementum was observed eight weeks after the injury and the two methods of miniscrew insertion showed no significant difference when it comes to the healing process.